The Short and Long Telomere Syndromes: Paired Paradigms for Molecular Medicine - Stanley, Susan E. (Curr Opin Genet Dev, 2015)
Recent advances have defined a role for abnormally short telomeres in a broad spectrum of genetic disorders. They include rare conditions such as dyskeratosis congenita as well pulmonary fibrosis and emphysema. Now, there is new evidence that some familial cancers, such as melanoma, are caused by mutations that lengthen telomeres. Here, we examine the significance of these short and long telomere length extremes for understanding the molecular basis of age-related disease and cancer.